Mobility testbed for 3GPP2-based multimedia domain networks. - Dutta, Ashutosh (IEEE Communications magazine)
Wireless service providers strive to preserve the quality of service and user experience for mobile users. Several standards bodies are defining architectures that can be used as a platform to provide secure and seamless services to these mobile users. These architectures aim to provide several required functions such as signaling, configuration, security association, encryption, and billing. However, the placement of several functional components and their interaction at several layers contributes to the operational complexity and thus affects the optimal results. Testbed realization of any standardized architecture can help investigate the underlying networking issues. In this article, we describe a mobility test bed implementation based on one of the architecture alternatives of 3GPP2, where the outbound signaling servers are distributed around the edges of the network. We experiment with three different hand-off techniques and analyze the associated experimental results. Analysis of these experimental results and experiences obtained from the testbed implementation can be helpful to any service provider that plans to deploy a version of the MMD (multimedia domain) architecture with distributed signaling servers.